Література для дітей та юнацтва: Краєзнавчий дискурс - Кизилова, Віталіна; Kyzylova, Vitalina (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті актуалізовано краєзнавчий компонент дослідження новітньої літератури для дітей та юнацтва. Зроблено акцент на жанровому розмаїтті творів для юного читача, їх пізнавальному, естетичному потенціалі. Наголошено на майстерності діалогу письменника з читачем-дитиною, оригінальності авторського бачення світу.The article emphasizes the regional component of investigation of modern Ukrainian literature for children and teen. The attention is focused on its genre’s polyphony (free verse, fable, palindrome, patter, story in verses, narrative in novels, riddleacrostic), cognitive and aesthetic potential. The works of I. Svitlychnyi, V. Goloborodko, G. Polovynkо, L. Strelnyk are intended for children and school age and junior pupils; they are characterized by original stylistics and delicate figurativeness. The works demonstrate kindness and optimism; cognitive and didactic components are shown in lyric. The authors have a delicate perception of a child, carry on a skillful dialogue showing their original vision of the world.
Literature for Children and Teen: Regional Survey
Keywords: література для дітей та юнацтва; жанр; жанровий різновид; краєзнавство; literature for children and teen; genre; genre variety; regional study